Pengaruh Budaya Organisasi dan Stres Kerja Terhadap Kinerja Karyawan Pada PT. BPR Syari’ah Lantabur Tebuireng di Jombang - Dwi Permatasari (BIMA : Journal of Business and Innovation Management, 2019)
PT. BPR Syari’ah Lantabur Tebuireng in Jombang is a banking financial institution in the Jombang region that first applied the syariah principle in its operational activities. The purpose of this study was todetermine the effec of organizational culture and work stress both partially or simultaneosly on employee performance. The approach used in this Study is a quantitative approach with a type of caussal research. The number of samples is 40 respondents who are permanent employees at PT. BPRS Lantabur Tebuireng in Jombang using saturated sampling techniques. This study uses questionnaire data collection techiques, interviews, documentation and observation. In data analysis using statistical methods using validity and reability tests, classic assumption tests and hypothesis tests using multiple linier regression tests. The resutls showed that organizational culture partially had a significant positive effect on the performance of employees of PT. BPRS Lantabur Tebuireng Jombang, work stress partially has a significant positive effect on employee performance at PT. BPRS Lantabur Tebuireng in Jombang, organizational culture and work stress simultaneously effect the performance of employess at PT. BPRS Lantabur Tebuireng in Jombang